2016
DOI: 10.1364/optica.3.000465
|View full text |Cite
|
Sign up to set email alerts
|

Light-emitting diode pumped luminescent concentrators: a new opportunity for low-cost solid-state lasers

Abstract: International audienceHigh-power light-emitting diodes (LEDs) today are twice as powerful as four years ago while meantime their price has been divided by 4 making them promising sources for laser pumping. However, their irradiance still falls short by one order of magnitude of what is needed to efficiently pump solid-state lasers. We demonstrate that an LED-pumped Ce:YAG luminescent concentrator (LC) can increase the irradiance of blue LEDs by a factor of 10, with an optical efficiency of 25%, making them muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 17 publications
0
38
0
Order By: Relevance
“…Recently [1][2][3][4][5], we developed a new type of LED-based light source, the high lumen density (HLD) source, which is very stable and enables the mentioned applications (luminance > 2·10 9 cd/m 2 ). Similar concepts were investigated by others [6,7].…”
Section: Introductionmentioning
confidence: 71%
“…Recently [1][2][3][4][5], we developed a new type of LED-based light source, the high lumen density (HLD) source, which is very stable and enables the mentioned applications (luminance > 2·10 9 cd/m 2 ). Similar concepts were investigated by others [6,7].…”
Section: Introductionmentioning
confidence: 71%
“…Fluorescence Lignum nephriticum ('kidneywood'), aragonite, and so on (in all the below cited luminescence types) [7] Display devices, fluorescent hydrogels, biomarkers Luminescence is a process having a wide range of applications in everyday life, starting from the conventional fluorescent lighting they extend to digital radiography in the field of magnetic resonance imaging (MRI) [27], electronic portal imaging device (EPID) [28], light-emitting diodes (LEDs) [29,30], solid-state lasers [31], luminescent solar concentrators [32] and many/ much other electrical and electronic equipment employ luminescent materials. Recently, electroluminescent display that shows promise for making flexible electroluminescent flat panel display (FEL-FPD) technology [33] is emerging worldwide; it also provides an excellent platform for a foundation for a no-compromise hang-on-the wall TV.…”
Section: Type Examples Applicationsmentioning
confidence: 99%
“…We have recently demonstrated that LED pumped luminescent concentrators (LC) are among the incoherent light sources with the greatest irradiance (several kW/cm² in pulsed regime [5]). Indeed, luminescent concentrators have the property to circumvent the brightness conservation rule with a process of absorption/emission in a high refractive index medium at the cost of a wavelength shift.…”
mentioning
confidence: 99%
“…Moreover, unlike direct LED pumping, LCs offer the potential of power scaling thank to the conversion of massive collection of LED beams into a small emitting area. Despite a cost in efficiency, this new kind of source benefits from all the advantages of the LED technology such as ruggedness, compactness, simplicity and low price [5][6][7]. For validation, LCs were used to pump rare-earth-doped crystals (Nd:YVO4 [5] and Nd:YAG [8]).…”
mentioning
confidence: 99%
See 1 more Smart Citation